2014
DOI: 10.1002/tox.22010
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the protective effects of proanthocyanidin and vitamin E against the toxic effect caused by formaldehyde on the liver tissue

Abstract: We aimed to investigate of protective role of proanthocyanidin (PA) and vitamin E (vit E) against to toxic effect of formaldehyde (FA). Twenty-eight Wistar albino rats were divided into four groups: control group, rats treated with FA intraperitoneal (i.p.) (10 mg/kg), FA + vit E intragastric (i.g.) (30 mg/kg), and FA + PA i.g. (100 mg/kg). We assayed superoxide dismutase (SOD), glutathione peroxidase (Gpx), myeloperoxidase (MPO) activity and levels of malondialdehyde (MDA) and total sialic acid (TSA) in liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…The amount of MDA was significantly decreased due to the effect of linoleic acid, suggesting the presence of oxidative stress in the culture medium. In this study, the quantity of MDA was significantly decreased with the administration of PA or HW [ 9 , 12 ], consistent with previous studies showing that the elevation of MDA level induced by lipid peroxidation was counteracted by the administration of PA or HW. Although the present study indicates that PA possesses higher anti-HBL effects compared with HW, no significant variation occurred in our study considering the dosage and duration of PA administration.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The amount of MDA was significantly decreased due to the effect of linoleic acid, suggesting the presence of oxidative stress in the culture medium. In this study, the quantity of MDA was significantly decreased with the administration of PA or HW [ 9 , 12 ], consistent with previous studies showing that the elevation of MDA level induced by lipid peroxidation was counteracted by the administration of PA or HW. Although the present study indicates that PA possesses higher anti-HBL effects compared with HW, no significant variation occurred in our study considering the dosage and duration of PA administration.…”
Section: Discussionsupporting
confidence: 92%
“…The LIN+PA group received a 100 mg/kg dose of PA diluted with potable water daily [ 12 , 13 ] and was injected with 0.5 mL of 60 mmol/L linoleic acid diluted in 20% ethanol by intravenous administration into the tail vein after 2 weeks of feeding [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formaldehyde is employed as one of the vital reactants in the production of trimethylolmelamine and accordingly, the addition of trimethylolmelamine into the formula of Pyrovatex results in the discharge of high level of formaldehyde . Regrettably, there are serious poisonous issues related to formaldehyde, including carcinogenicity, skin and eye irritation, headache and problems in the respiratory system . Therefore, a formaldehyde free alternatives, such as 1,2,3,4‐butanetetracarboxylic acid has been tested with flame‐retardant in presence of sodium hypophosphite as a catalyst in order to improve the flame retardancy and durability.…”
Section: Introductionmentioning
confidence: 99%
“…Current research on the toxicity of FA has in-depth damage in the liver, and FA induced liver injury model of research in recent years is also very mature [21, 22]. Such that Bakar et al [23] found that FA markedly increased cell apoptosis in the liver.…”
Section: Introductionmentioning
confidence: 99%